On New Types of Weakly Neutrosophic Crisp Open Mappings - Al-Obaidi, Ali Hussein Mahmood; Imran, Qays Hatem (Iraqi Journal of Science, 2021)
This work employs the conceptions of neutrosophic crisp a-open and semi-a-open sets to distinguish some novel forms of weakly neutrosophic crisp open mappings; for instance, neutrosophic crisp a-open mappings, neutrosophic crisp a*-open mappings, neutrosophic crisp a**-open mappings, neutrosophic crisp semi-a-open mappings, neutrosophic crisp semi-a*-open mappings, and neutrosophic crisp semi-a**-open mappings. Moreover, the close connections between these forms of weakly neutrosophic crisp open mappings and the viewpoints of neutrosophic crisp open mappings are explained. Additionally, various theorems and related features and notes are submitted.